STRATEGI PENERJEMAHAN DAN PERGESERAN MAKNA KOSAKATA BUDAYA MATERIAL PADA NOVEL DENSHA OTOKO KARYA NAKANO HITORI SERTA TERJEMAHANNYA DALAM BAHASA INDONESIA - Suryawati, Anak Agung Sagung (Humanis, 2016)
Knowledge about culture is one of the important things that translators should have because one of the difficulties in translating is to translate text with material cultural words. This research discusses about translation strategies and shift of meaning of material cultural words in the novel Densha Otoko by Nakano Hitori and its Indonesian version, Train Man by Kanti Anwar. The data analysed using descriptive method. This research used the theory of translation strategies by Baker (1992) and componential analysis by Bell (1993). There are five strategies of translation that used to translate the material cultural words. Translation strategy using cultural substitution caused the shift of meaning. The categories of material cultural words that have shift of meaning are the categories of food, clothes, house, and town.
Keywords: material cultural words, translation strategies, shift of meaning